Pengaruh Model Quantum Learning Berbasis Masalah Kontekstual Terhadap Kemampuan Berpikir Kreatif Siswa SMA - Ni Luh Putu Swandewi; I Nyoman Gita; I Made Suarsana (Jurnal Elemen, 2019)
This study aims to determine whether students' mathematical creative thinking skills that are taught with a quantum learning model based on contextual problems are better than mathematical creative thinking abilities that are taught with conventional learning. The population of the study was students of class XII MIPA SMA 2 Singaraja in the first semester of 2018/2019 academic year. The research sample was determined by cluster random sampling technique. This research was categorized as quasi-experimental research with post-test only control-group design research design. Data about the ability of students' creative thinking skills were collected through tests of students' mathematical creative thinking skills. Furthermore, the test scores of the ability to think mathematically creative were analyzed using the t-test of one tail (right tail) at a significance level of 5%. The results of the analysis show that tcount = 1.80295 while the significance level of 5% is obtained ttable = 1.66864, so H0 is rejected. This statistical value means that students' mathematical creative thinking skills that are taught with contextual problem-based quantum learning models are better than students' creative thinking abilities that are taught with conventional learning. It can be concluded that the application of learning with contextual problem-based quantum learning models provides a positive influence on students' mathematical creative thinking skills.